One hundred houses for one hundred architects : 100 houses for 100 architects. - Postiglione, Gennaro, ....-; Acerboni, Francesca, ....-; Canziani, Andrea, ....- (Köln : Taschen, 2008)
Het is bijzonder interessant om de huizen te onderzoeken die architecten voor zichzelf creren. Als huizen de persoonlijkheden van hun bewoners weerspiegelen, dan zijn de huizen van architecten autobiografien. Locatie, lay-out, stijl, verlichting, kunstwerken, meubels - ieder detail voegt kleur toe aan het verhaal. Elk van deze 100 huizen, die per architect van A tot Z worden gepresenteerd, zegt meer over de ontwerper dan welk ander gebouw dan ook zou kunnen. - When architects design their own homes, they become their own dream clients. For anyone intrigued by the possibilities of domestic architecture, One Hundred Houses for One Hundred European Architects of the Twentieth Century initially seems as if it will be a fascinating entr into the private worlds leading modern architects have built for themselves. Beginning with the great Finnish modernist Alvar Aalto and ending with John Young, an Englishman best known for his high-tech designs for airports, the book includes famous figures
(Le Corbusier, Eileen Gray, Victor Horta, William Morris, Otto Wagner) as well as architects unknown outside specialist circles. Each house is illustrated with a floor plan and exterior and interior photographs--many in color--and each architect's major projects are listed, along with brief bibliographies. So far, so good. Unfortunately, many of the brief individual essays are written in stiff, bureaucratic prose with all the earmarks of a bad translation. The numerous authors offer up facts without relating the homes to the lives and design philosophies of the architects in vivid and insightful ways. Editor Gennaro Postiglione's terse and stilted introduction is equally disappointing. As if to acknowledge these problems, the book is printed in hard-to-read gray type. Still, some of the entries offer more personal glimpses. When Swedish architect Gert Wing¥rdh enlarged an 18th-century farmhouse by adding two subtly-angled wings, he managed to combine his seemingly contradictory love of traditional
Materials and Venturian complexity with "green" technology--still in its infancy in 1990. Working with wood, a peat and grass-covered roof, and floors of limestone or pine, he achieved a sensual harmony of forms and spaces.
Keywords: Architecten; Huizen